Determinação da estrutura tridimensional de um inibidor de serinoproteases do tipo Kazal do mosquito aedes aegypti, vetor da dengue - Torquato, Ricardo Jose Soares [UNIFESP] (2018)
The mosquito Ae. aegypti is the main vector of arboviruses for humans in Brazil and it is responsible for outbreaks of dengue, chikungunya, yellow fever, and recently it has been involved in the high number of humans infected with zika virus. The hematophageal activity of Ae. aegypti allowed it to develop several strategies to control the hemostasis of vertebrate host’s. In 2010, our group expressed and characterized a serinepeptidase inhibitor belonging to Kazal family called rAaTI (Aedes aegypti Trypsin Inhibitor). The purified rAaTI was able to inhibit trypsin and affect coagulation time. With this data, the present work had as general objective the determination of three-dimensional structure of AaTI to understand its role in prolonging coagulation time. The rAaTI was purified in amount and an inhibitor preparation containing 20 mg/mL presenting high degree of homogeneity was used in crystallization experiments. The rAaTI crystallized in 100 mM sodium acetate, pH 5.5 containing 25% PEG 3350, 5% PEG 400 and 3% dioxane. Some crystals of rAaTI were dipped in sodium iodide solution with different concentrations (soaking) for 10 s to 1 min, and then they were analyzed (diffracted) on the MX2 line at the National Synchrotron Light Laboratory (LNLS), Campinas. The three-dimensional structure of rAaTI was determined at high resolution of 1.4 Å. The unit cell of the crystal had an unusual low solvent content of approximately 22-23% (Torquato et al., 2017), accommodating two molecules of rAaTI. rAaTI has previously been described as inhibitor of serine protease, bovine trypsin (Ki = 0.15 nM) and human plasmin (Ki = 3.8 nM), and with anticoagulant activity, prolongating the coagulation time, including time of thrombin (TT) (Watanabe et al., 2010). In an attempt to clarify where rAaTI binds to the surface of thrombin, some experiments were performed using surface plasmon resonance (SPR) technology. Thrombin was immobilized on the surface of the CM5TM GE sensorchip. Different concentrations of rAaTI were applied to the surface containing immobilized thrombin and it was obtained a dissociation constant (KD) of 3.68 μM. Watanabe et al. showed a value of KD = 320 nM (Watanabe et al., 2011). The dissociation constant calculated by SPR is approximately ten times higher, which can be explained by partial blocking of thrombin exosites I and II during the enzyme immobilization procedure. The SPR experiments showed inhibition of the binding of rAaTI to thrombin in the presence of heparin, reinforcing the suggestion that AaTI can interacted to exosite II of thrombin.